a2+5a-4a=6

Subtract 4a from 5a.

a2+a=6

Move 6 to the left side of the equation by subtracting it from both sides.

a2+a-6=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -6 and whose sum is 1.

-2,3

Write the factored form using these integers.

(a-2)(a+3)=0

(a-2)(a+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

a-2=0

a+3=0

Set the first factor equal to 0.

a-2=0

Add 2 to both sides of the equation.

a=2

a=2

Set the next factor equal to 0.

a+3=0

Subtract 3 from both sides of the equation.

a=-3

a=-3

The final solution is all the values that make (a-2)(a+3)=0 true.

a=2,-3

Solve for a a^2+5a-4a=6